Human Immunodeficiency Virus 1 and Type I Interferons—Where Sex Makes a Difference - Ziegler, Susanne Maria; Altfeld, Marcus (Frontiers in Immunology, 2017)
The human immunodeficiency virus (HIV)-1 epidemic continues to represent a global health problem that is over-proportionally affecting women from sub-Saharan Africa. Besides social and environmental factors, the modulation of immunological pathways by sex hormones and gene dosage effects of X chromosomal-encoded genes have been suggested to lead to differential outcomes in HIV-1 disease. Women present with lower HIV-1 loads early in infection, however, the progression to AIDS for the same level of viremia is faster in women than in men. Type I interferons play a prominent role in the control of HIV-1 transmission and replication. Continuous stimulation of type I interferons in chronic viral infections can lead to increased levels of immune activation, which is commonly higher in HIV-1-infected women than in men. A role of steroid hormone signaling in regulating viral replication has been postulated, which might further account for sex-differences observed in HIV-1 infections. Here, we review recent findings and current knowledge on sex-specific differences in HIV-1 infections.